Apprehension and Understanding of the Health Needs Concept for Students of an Active Curriculum - Nonato,Ana Carolina (2020)
Abstract: Introduction: The 2001 National Curriculum Guidelines value the biopsychosocial aspects of the health-disease process and student accountability through training and active performance in health services. This study was carried out at a college in the countryside of the state of São Paulo, which has the concept of health needs as a theoretical guide. To understand the experience of medical and nursing students in relation to the concept and operationalization of the integrated curriculum. Theoretical-practical developing of the relationship between students and other health actors was carried out to identify reasons for the divergence in the understanding of the theoretical framework between them, providing subsidies to identify these inequalities in the context of teaching. Methods: 33 students from the aforementioned courses were interviewed. The study was performed using the methodological framework of Grounded Theory and theoretical context of health needs. The semi-directed interviews were recorded, transcribed in full and coded line by line, according to the microanalysis process. The codes were grouped into elements, subsidies for the creation of categories. Results: There were five emerging categories: (1) “Understanding that there are differences in approach between the groups of the Systematized Educational and Professional Practice Units and between the educational units, with difficulties for effective theoretical-practical articulation”; (2) “Identifying that there is a discrepancy in learning and experiences of the concepts of health needs among students”; (3) “Understanding that the apprehension of health needs is more effective when theory is associated with practice and vice versa”; (4) “Assimilating that the concept of health needs is related to the extension of the integrality of care focus” and (5) “Recognizing the link as essential in the school years and teaching-learning scenarios to identify health needs and practical care success”. These constitute the theoretical model: “According to the student’s perspective, the apprehension and understanding of health needs depend on the theoretical-practical articulation in the different groups of students and teaching-learning scenarios, having as essential elements the link and the integrality of care”. Final considerations: For the effective apprehension of students’ health needs, discontinuity of learning and discrepancies in how it is conducted must be avoided, a process that depends on links and comprehensive care in order to be viable.